COMPARISON OF COLLABORATION PATTERNS AMONG ACTORS INNOVATION IN HANURA VILLAGE, TELUK PANDAN SUB-DISTRICT, PESAWARAN REGENCY, AND TARAHAN VILLAGE, KATIBUNG SUB-DISTRICT, SOUTH LAMPUNG REGENCY, LAMPUNG PROVINCE. - Rahmawati Ahfan; Achlami HS; Sonhaji .; Rini Setiawati (Saburai International Journal of Social Sciences and Development, 2022)
Village innovation is a necessity for accelerating rural development given the current problems faced by villages, including: (1) limited infrastructure; (2) limited accessibility in the form of capital, land, production inputs, and marketing networks; (3) uncertainty of local commodity prices; and (4) fragmented village development programs. The purpose of this study is to analyze actor collaboration in village innovation as a model for developing Islamic communities. This study is a descriptive study using a qualitative approach. The study was conducted in Hanura Village, Teluk Pandan District, Pesawaran Regency, and Tarahan Village, Katibung District, South Lampung Regency, Lampung Province. Data sources were selected purposively and through snowball sampling, including village officials, religious figures, community leaders, and social activists. Data collection used interview and observation techniques, which were then analyzed by data reduction, data presentation, drawing conclusions, and examining data validity through source, technique, and time triangulation. The results showed that there were three patterns of actor collaboration in village innovation: leadership collaboration, team process collaboration, and cultural collaboration. The Hanura Village innovation focused more on leadership and team process collaboration, while the actor collaboration in Tarahan Village innovation relied more on cultural collaboration.